A model-scale study to assess the influence of ground geometries on aerodynamic flow development around a train. (September 2017) - Soper, David; Gallagher, Martin; Baker, Chris; Quinn, Andrew
The need for interoperability for rail operators across Europe has resulted in the development of the technical specifications for interoperability: requirements and regulations which include safety limits for train aerodynamics. Safety limits are calculated within guidelines, including environmental conditions, train speeds and ballast shoulder height. However, there are many cases on the European rail network which fall outside ballast shoulder height limits, raising questions about the suitability of the technical specifications for interoperability limits, where European homologation is a requirement. Ballast is a layer of crushed stone onto which the railway track is laid; a ballast shoulder is defined from the top of the ballast layer to the base of the track foundation or ground. This paper describes the detailed model-scale experiments carried out at the University of Birmingham's moving model TRAIN rig facility to assess the influence of ground geometries on aerodynamic flow development around a train. The technical specifications for interoperability methodology was questioned in relation to whether modest changes to include a wider cross-section of ballast shoulder heights, more appropriate to actual operating conditions, would affect limit values in relation to safety. The influence of ballast shoulder height was investigated for three typical train types. The results showed a similar static pressure development for all the ballast shoulder heights tested. Passenger train results indicated that shallow ballast shoulders confine the aerodynamic flow within a smaller area, increasing the magnitude of slipstream velocities in respect to larger ballast shoulders. The largest slipstream velocities were found for the ground configuration with no ballast shoulder modelled. Measurements within the technical specifications for interoperability-specified range of ballast shoulder heights exhibited little difference in flow development. Analysis of maximum 1 s gusts, calculated using the current technical specifications for interoperability methodology, found values lie close to, but do not break, the existing limits. Increasing ballast shoulder height was shown to decrease values away from technical specifications for interoperability limits.